The comparative analysis of the methods of calculating the icebreaking capability of icebreakers - ZINEVICH ANDREY; KITAEV MAKSIM (Zenodo, 2017)
When designing icebreakers and ice ships, the most important is their icebreaking capability which determines the efficiency of each individual vessel. Nowadays, there are many empirical approaches enabling one to carry out a numerical assessment of the performance characteristics of icebreakers in solid ice. Those approaches differ by the amount of parameters of the shape of the vessel’s hull and by the reliability of the obtained results. The article presents the results of the comparative analysis of the existing methods of calculating the resistance of the motion of the ship in solid ice. Considered are the empirical methods advanced by V.I. Kashtelyan, D.D. Maksytov, O.V. Fadeev, G. Lindqvist, K. Risca, Ju. I. Voitkunsky, a.o. The authors have compared the result of calculations with the published data of full-scale and simulated tests of the icebreakers Ermak and Moskva .